2014
DOI: 10.1021/es4050067
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decomposition of Toxic Chemicals Over Iron Group Metals Supported on Carbon Nanotubes

Abstract: This study explores catalytic decomposition of phosphine (PH3) using iron group metals (Co, Ni) and metal oxides (Fe2O3, Co(3)O4, NiO) supported on carbon nanotubes (CNTs). The catalysts are synthesized by means of a deposition-precipitation method. The morphology, structure, and composition of the catalysts are characterized using a number of analytical instrumentations, including high-resolution transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, BET surface area measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…The peaks at 707.4 and 129.5 eV are close to the BE for Fe and P in FeP [36]. The peaks at 711.9 and 133.6 eV can be assigned to oxidized Fe and P species arising from superficial oxidation of FeP exposed to air [37]. The Fe 2p BE of 707.4 eV is positively shifted from that of metallic Fe (706.8 eV) [38], indicating Fe in FeP carries a partial positive charge (d þ ).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The peaks at 707.4 and 129.5 eV are close to the BE for Fe and P in FeP [36]. The peaks at 711.9 and 133.6 eV can be assigned to oxidized Fe and P species arising from superficial oxidation of FeP exposed to air [37]. The Fe 2p BE of 707.4 eV is positively shifted from that of metallic Fe (706.8 eV) [38], indicating Fe in FeP carries a partial positive charge (d þ ).…”
Section: Resultsmentioning
confidence: 67%
“…While the P 2p BE of 129.5 eV shows negative shift from that of elemental P (130.2 eV) [39], suggesting P in FeP carries a partial negative charge (d À ). The results suggest electron transfer from Fe to P [36,37,40]. It is reported that hydrogenases use pendant bases proximate to the metal centers as active sites for hydrogen evolution [41] and metal complex HER catalysts also incorporate proton relays from pendant acidebase groups close to the metal center where hydrogen evolution occurs [42e44].…”
Section: Resultsmentioning
confidence: 99%
“…1,3 Platinum (Pt) is still the most efficient electrocatalyst for HER, however, the high cost and limited supply of Pt necessitate finding an alternative cheap and abundant catalyst for HER applications. 4 A series of well-known hydrodesulfurization (HDS) catalysts were shown to be excellent catalysts for HER, such as Ni 2 P, 5-7 NiS 2 , 8,9 CoP, 10-13 WP, 14,15 FeP, [16][17][18] CoSe 2 , 19 MoP, 20-23 Mo 2 C, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and MoS 2 . [39][40][41][42][43][44][45][46] Molybdenum is much more abundant than Pt and the United States produces the most molybdenum in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant N-doped carbon hybrids, which possessed high Brunauer-EmmettTe ller (BET) surface area as well as appropriate pore volumes and pore diameters, could serve as highly efficient metal-free heterocatalysts with very good catalytic activity as well as generality and couldb ee asily recovered without any compromise of catalytic performance.Functional mesoporous carbon materials have attracted much attentioni nr ecent years and are widely employed for energy storage, separation technologies, ande lectrochemistry owing to their large specific surface areas, adjustable pore size, excellent stabilitya nd conductivity.[1] However, as an efficient catalyst, appropriate and sufficienta ctive sites are also required in addition to these outstanding features.[2] Therefore, heteroatoms, especially nitrogen atoms, were incorporated into the carbon matrix to improve the catalytic performance of active sites or to directly serve as active sites for corresponding reactions.[3] Recently,n itrogen-doped carbon materials were widely reported as supports for metals or their oxides in variousr eactions including oxidation, [4] dehydrogenation, [5] hydrogenation, [6] hydrochlorination, [7] Fischer-Tropschs ynthesis, [8] andt he decomposition of toxic chemicals, [9] and the incorporation of nitrogen atoms significantly enhanced the catalytic activity of these metalso rt heir oxides. However,t he high price and the possible contamination of metal catalysts greatly limited their applications.…”
mentioning
confidence: 99%
“…[3] Recently,n itrogen-doped carbon materials were widely reported as supports for metals or their oxides in variousr eactions including oxidation, [4] dehydrogenation, [5] hydrogenation, [6] hydrochlorination, [7] Fischer-Tropschs ynthesis, [8] andt he decomposition of toxic chemicals, [9] and the incorporation of nitrogen atoms significantly enhanced the catalytic activity of these metalso rt heir oxides. However,t he high price and the possible contamination of metal catalysts greatly limited their applications.…”
mentioning
confidence: 99%